Relationship of Molecular Structure to the in Vivo- Distribution of Carbon-11-Labeled Compounds V. Carbon-11-Labeled N-Alkyl-p-Iodobenzenesulfon- amides - Winstead, M. B.; Dischino, D. D.; Winchell, H. S. (Nuklearmedizin - NuclearMedicine, 1979)
Carboni 1-labeled HCN was collected in methanol containing carrier NaCN following bombardment of 99% N2 - 1 % H2 with 22 MeV protons. Ten new N-alkyl-p-iodobenzenesulfonamides were synthesized and labeled with 11C in radiochemical yields averaging 27 % by condensation of p-iodobenzenesulfonyl chloride with the 11C-labeled aliphatic amine obtained by reduction of the intermediate 11C-labeled aliphatic nitrile prepared from Na 11CN and the corresponding alkyl bromide. They were chemically characterized and for nine of them the relationship between their molecular structure and their in vivo-distribution in rats was studied. As the length of the alkyl chain was increased from 2 to 8 carbon atoms, the early concentration of activity in most viscera decreased and the urinary excretion increased. Within this range, chains containing an even number of carbon atoms showed greater early tissue concentration of activity than did chains containing an odd number of carbon atoms. For alkyl chains containing greater than 8 carbon atoms the concentration of activity in some tissues increased and urinary excretion decreased. A possible explanation for the results is offered which postulates that early tissue concentration of activity is related to both total lipophilicity of the sulfonamide as well as to the presence of tissue sulfonamide binding sites whose preferred conformation results in hindered binding of sulfonamides with odd-numbered aliphatic chains to a greater extent than with even-numbered aliphatic chains.